Design and development of a teleoperated mobile robot with SLAM and thermal sensing - Mohd, Zaid; Najib, Akmal Zarif; Khan, Mazbahur Rahman; Mohd Ibrahim, Azhar (Springer Nature, 2026)
Mobile robots are now widely used in many areas such as industry, monitoring, and rescue operations. A common problem is that most robots either focus on mapping or sensing, but not together in one simple system. The aim of this research is to design and develop a customized mobile robot that can do Simultaneous Localization and Mapping (SLAM) while also using a thermal camera for non-contact temperature measurement and thermal imaging. The method involves two parts: simulation and hardware implementation. The simulation was done using robotic firmware, and the hardware was designed in SolidWorks and built with sensors including LiDAR, IMU, and a thermal camera. The robot is controlled by teleoperation, which allows manual navigation while collecting temperature data and creating maps in real time. The results show that the system can display mapping and temperature information on an onboard LCD and a remote workstation. The significance of this finding is that the proposed system provides a reliable way to combine teleoperation, temperature detection, and mapping in one robot, with possible use in hazardous environments, industrial monitoring, and inspection tasks.